PEMIKIRAN EKONOMI IBNU KHALDUN (732-808 H / 1332-1404 M) - Hamid, Azwar (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
Abstract Ibnu Khaldun is one of the influenced person in Islamic Economy. He contributes much in Islamic economy. It is proven by his economic thoughts which applied by many people. These thoughts can be learned from his book entitle Muqaddimah. Some of the thought that can be gained is market system, profit without riba, unemployment decreasing concept, production theory and so on. Ibnu Khaldun struggles for the human right and the government objection to the people without any violence. In the other words, it can be said that he offers Islamic justice. Keywords: Ibnu Khaldun, Islamic Economy, Market System